Environmental awareness and its relationship to some variables among sixth grade students in Koysinjaq district - Eman Bahnam Aboo; Shiereen Kareem Ali; Dastan tareq faeeq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
. The goals: The current research aims at a range of goals including: Measuring environmental awareness among the sixth grade students in Queseng Are there statistical differences between the environmental awareness and the school variable among the sixth grade students in Quesengq? Are there statistical differences between the environmental awareness and variable and the educational achievement of parents among the sixth grade students in Quesengq? Are there statistical differences between the environmental awareness and the father's career variable among the sixth grade students in Quesengq? The importance: The attention to the environment in our time has become an urgent demand, as a result of the large population increase and the aggravation of the problems of environmental pollution and the resulting dangers to the environment and thus to human health has made the solutions random and short-term is not effective to solve environmental problems, but to find a radical solutions to the problems that cause the environment and here Environmental thought emerged and global attention increased day after day. Environmental education and environmental awareness became necessary for the children of this era. The Plan: The study plan was prepared by following up the environmental problems and preparing a measure of environmental awareness commensurate with the age of the students of the sixth grade. The sample of the study was 233 students distributed in five schools in the district of Quesengq (Beshwa Primary Mixed School, (Mixed), Najeeba Khan mixed elementary school, Sherin primary mixed school (the coefficient of stability was alpha kronbach (0.80), This indicates the coefficient of good stability and the results were found using the statistical means of the package (SPSS). The suggestions: 1 - Take care of raising children and accustom them to deter bad behaviors such as waste water, electricity and waste disposal elsewhere and others. 2. To carry out school trips aimed at instilling green values in them, increasing their environmental awareness, and encouraging interest in the environment.